Writing business letters how to produce day-to-day correspondence that is clear and effective - Dobson, Ann (Golden Books Centre, 2000)
Aimed at newcomers and returners to work this guide will train them to cope with basic business letter-writing. Using many examples it shows the basic skills in planning a letter, writing and answering complaints, personal and standard letters, job applications and many more.